"Stepdogs" of society: the impact of breed bans in Norway - Lie, Martine S. B. (Critical criminology, 2017)
Drawing on qualitative interviews with dog owners and police officers, this article discusses the ban against "dangerous dogs" in Norway. The Norwegian breed ban in The Dog Regulation (hundeforskriften) is shown to have considerable negative influence on affected dogs’ lives, even if their owners do their best to compensate for this. Labeling, stigmatization and risk of confiscation by the police has restricted aspects of the dogs’ lives, such as by complicating their opportunities to be with fellow species. The impact of breed-specific legislation on dogs is analyzed from a critical, anti-speciesist perspective, which sees modern Western societies and their judicial systems as characterized by an inherent discriminatory culture and order. This oppression entails both differential treatment of disadvantaged humans’ and humans’ repressive and differentiating attitudes and actions towards other animals.